2022
DOI: 10.30656/jsmi.v6i2.5051
|View full text |Cite
|
Sign up to set email alerts
|

The effect of safety leadership, safety culture, and safety behavior on safety performance after a company merger: a case study

Abstract: After the merger of PT Pelindo, PT Pelindo Terminal Petikemas became one of the sub-holding companies in containers. In maintaining consistency with the implementation of Occupational Health and Safety (OHS) after the merger, PT Pelindo Terminal Petikemas needs to understand the importance of safety leadership, safety culture, safety behavior, and safety perfor­mance in the OHS program's success. The study aimed to determine the effect of safety leadership on safety culture and safety performance, the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This is in line with research conducted at a container management company, which found that leadership had a significant impact on safety culture. Thus, if the leadership at a company is good, a better safety culture may be developed (Atikasari et al, 2022).…”
Section: The Impact Of Leadership On Safety Culture Maturity Levelmentioning
confidence: 99%
“…This is in line with research conducted at a container management company, which found that leadership had a significant impact on safety culture. Thus, if the leadership at a company is good, a better safety culture may be developed (Atikasari et al, 2022).…”
Section: The Impact Of Leadership On Safety Culture Maturity Levelmentioning
confidence: 99%
“…Safety culture was defined as the perceptions of employees regarding safety conditions and their impact on safety outcomes [7]. Meanwhile, safety leadership had a substantial impact on safety culture, and in turn, safety culture significantly influenced safety performance [8]. Safety competency holds paramount importance across various industries, directly impacting both individual well-being and overall organizational success [9].…”
Section: Introductionmentioning
confidence: 99%